Les campagnes de la France méditerranéenne dans l'Antiquité et le haut Moyen Âge Étude microrégionales - Favory, François; Fiches, Jean-Luc (Documents d'archéologie française, 1994)
This volume is an evaluation of ten years' activity of a group of archaeologists and historians, organised into pluridisciplinary teams, who devote their energies to characterising the forms of rural habitat in Gallia Narbonensis and their evolution front the Roman Conquest to the Middle Ages. Without claiming to give final results in this book, set end teams are particular about presenting an unpublished information which states precisely the nature of the habitat identified through survey and excavation, the date of its establishment and duration of its occupation, and also different data about its relation with environment. Here you can find contributions dealing with the antique rural habitat in East Languedoc, in the middle Rhône valley, in the area framed by landregister B of Orange and in Provence-Côte-dʼAzur.